2004
DOI: 10.1111/j.1365-2966.2004.07169.x
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale alignment of optical polarizations from distant QSOs using coordinate-invariant statistics

Abstract: We introduce several coordinate-invariant statistical procedures in order to test for alignment of polarizations of electromagnetic radiation from astrophysical sources. A large-scale alignment of optical polarizations from distant quasi-stellar objects (QSOs) has recently been observed by Hutsemékers and collaborators. The new statistical procedures are based on comparing polarizations at different angular coordinates by making a parallel transport. The results of these statistical procedures continue to supp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
142
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(153 citation statements)
references
References 23 publications
(34 reference statements)
11
142
0
Order By: Relevance
“…We solve the Eqns (7)(8)(9)(10)(11)(12) by use of standard techniques [20]. The results for the long wavelength mode being both subhorizon and superhorizon during present time are standard results of the text.…”
Section: Matter Density Perturbationmentioning
confidence: 99%
See 2 more Smart Citations
“…We solve the Eqns (7)(8)(9)(10)(11)(12) by use of standard techniques [20]. The results for the long wavelength mode being both subhorizon and superhorizon during present time are standard results of the text.…”
Section: Matter Density Perturbationmentioning
confidence: 99%
“…While u 2 = 1/3 during radiation domination, it is zero during matter domination. The solutions for superhorizon mode potentials of Eqn (12) shows that the potential is effectively constant and equal to the initial value at each epoch. We calculate the values of the density contrast in different component by making use of the curvature perturbation, ζ( r), which remains constant.…”
Section: Mode Superhorizonmentioning
confidence: 99%
See 1 more Smart Citation
“…A weakness of the tests used in Paper I was their dependency upon the coordinate system. Jain et al (2004) −4 we used up to 10 5 simulations. Significance levels are given in Fig.…”
Section: Global Statisticsmentioning
confidence: 99%
“…It was found and confirmed that the quasar polarization vectors are not randomly oriented as naturally expected, but appear concentrated around one preferential direction on very large spatial scales [11][12][13][14]. The polarization vectors appear coherently aligned over huge (∼ Gpc) regions of the sky located at both low (z ∼ 0.5) and high (z ∼ 1.5) redshifts and characterized by different preferred directions of the quasar polarization.…”
Section: Introductionmentioning
confidence: 72%